The Failure of Ronald Dworkin’s Philosophical Revolution - Jokubaitis, Alvydas (Problemos, 2014)
The aim of the paper is to prove that the philosophical revolution attempted by Dworkin in his book Justice for Hedgehogs ended as a failure. There are two reasons why this revolution did not succeed. First, Dworkin’s critique of the influence that science has on ethics is closely dependent on the scientific perspective. The author criticizes the subjugation of ethics by science and still wants to link it with science. Second, Dworkin’s critique of metaethics is too narrow, he confines himself to polemics with external scepticism which was imposed on it by scientific epistemology. Metaethics is a philosophical mistake of a much bigger scale than Dworkin thinks. Science plays an influence not only on ethical theories, but also on the level of “ordinary view”. Dworkin declares the philosophical revolution that does not deserve the name of a revolution. It is only a proposal to return to the earlier philosophical revolutions, those that are associated with the names of Hume and Kant. Theoretical attachment to Hume’s moral philosophy makes Dworkin’s philosophical critique less radical. He criticizes the principles of scientific epistemology that were imposed on ethical theory and at the same time he is not hiding his sympathy for science. This is a great inconsistency of his philosophical views. Not only does he defend the independence of ethics from scientific epistemology, but he also highlights the importance of the links between ethics and science. This position results in a halfway character of his philosophical critique. Moreover, Dworkin operates according to a too narrow Anglo-Saxon critique of metaethics. He does not mention the demoralizing impact this discipline has on practical understanding of morals.